Systematic Review of Capnography with Mask Ventilation during Cardiopulmonary Resuscitation Maneuvers - Francisco José Cereceda-Sánchez (Journal of Clinical Medicine, 2019)
The latest guidelines identify capnography as an instrument used to assess bag-valve-mask ventilation during cardiopulmonary resuscitation (CPR). In this review, we analyzed the feasibility and reliability of capnography use with face mask ventilation during CPR maneuvers in adults and children. This systematic review was completed in December 2018; data for the study were obtained from the following databases: EBSCOhost, SCOPUS, PubMed, Índice Bibliográfico Español en Ciencias de la Salud (IBECS), TESEO, and Cochrane Library Plus. Two reviewers independently assessed the eligibility of the articles; we analyzed publications from different sources and identified studies that focused on the use of capnography with a face mask during CPR maneuvers in order to describe the capnometry value and its correlation with resuscitation outcomes and the assistance of professionals. A total of 888 papers were collected, and 17 papers were included that provided objective values for the use of capnography with a mask for ventilation. Four were randomized clinical trials (RCT) and the rest were observational studies. Four studies were completed in adults and 13 were completed in newborns. After the analysis of the papers, we recommended a capnographic level of C in adults and B in newborns. Despite the little evidence obtained, capnography has been demonstrated to facilitate the advanced clinical practice of mask ventilation in cardiopulmonary resuscitation, to be reliable in the early detection of heart rate increase in newborns, and to asses in-airway patency and lung aeration during newborn resuscitation.